2017
DOI: 10.1017/rdc.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of the Middle Holocene High Sea-Level Stand and Climatic Changes on Mangroves of the Jucuruçu River, Southern Bahia – Northeastern Brazil

Abstract: The aim of this paper is to evaluate the compatibility between the Holocene relative sea-level (RSL) curves proposed for the Brazilian littoral and mangrove dynamics along a fluvial valley in the state of southern Bahia. This was done integrating geomorphological, sedimentological, palynological, and stable isotopic data from two cores collected at the mouth of the Jucuruçu River and at a site 23 km inland, near the city of Prado, northeastern Brazil. Core PR07, sampled from a fluvial plain at about 4.5±1 m ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
0
21
0
1
Order By: Relevance
“…Considering a RSL higher than the modern one and a stable fluvial discharge during the middle Holocene, mangroves would have expanded on flood plains and accumulated organic mud banks in higher topographic zones above the modern tidal range. Such a situation was recorded in a floodplain of the Jucuruçu River, near the city of Prado‐Bahia, north‐eastern Brazil, 23 km distant from the coastline, where a stratigraphic succession revealed the presence of an estuarine system with tidal flats colonized by mangroves and sedimentary organic matter sourced from estuarine organic matter 3.4 ± 1.35 m above the modern mangrove zone during the middle Holocene (Fontes et al, ).…”
Section: Interpretation and Discussionmentioning
confidence: 92%
“…Considering a RSL higher than the modern one and a stable fluvial discharge during the middle Holocene, mangroves would have expanded on flood plains and accumulated organic mud banks in higher topographic zones above the modern tidal range. Such a situation was recorded in a floodplain of the Jucuruçu River, near the city of Prado‐Bahia, north‐eastern Brazil, 23 km distant from the coastline, where a stratigraphic succession revealed the presence of an estuarine system with tidal flats colonized by mangroves and sedimentary organic matter sourced from estuarine organic matter 3.4 ± 1.35 m above the modern mangrove zone during the middle Holocene (Fontes et al, ).…”
Section: Interpretation and Discussionmentioning
confidence: 92%
“…Not all changes in coastal vegetation may be attributed to autogenic processes. For instance, a previous publication (Fontes et al, ) based on a multi‐proxy analysis of one core (core PR07) located 23 km from the mouth of the Jucuruçu River (Figure B) revealed that the landscape was an estuarine system with tidal flats colonized by mangroves between ~7450 and ~5500 cal yr bp . During the past ~5500 cal yr bp , the mangroves shrank and herbaceous terrestrial vegetation expanded.…”
Section: Interpretation and Discussionmentioning
confidence: 98%
“…Considering core PR07 was sampled from a floodplain with herbaceous vegetation positioned about 4.5 ± 1 m above the relative sea‐level (RSL), this environmental change may signify a progressive rise in RSL, with the consequent marine incursion into the Jucuruçu River valley during the early to middle Holocene. Conversely, during the late Holocene, RSL fell, causing marine regression and the restriction of mangroves to the tidal flats near the modern coastline (Fontes et al, ).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Mangrove forests appear to have back-stepped on the Great Barrier Reef, and the Belize barrier reef in the western Caribbean, where mangrove peats are preserved on the shelf beneath lagoonal sediments (Grindrod et al, 1999). Basal transgressive organic-rich peaty mangrove muds occur at the base of cores through coastal plains in southeast Asia and northern Australia (Woodroffe, 1993), as well as in eastern Brazil (Fontes et al, 2017). It will be shown below that about 8,000 years ago mangrove sedimentation was unable to keep pace with sea-level rise on open coasts, with mangrove forests back-stepping landwards, impinging on the hinterland ecosystems.…”
Section: Mangrove Responsementioning
confidence: 99%
“…Radiocarbon ages on mangrove material have provided much of the evidence for the trajectory and rates of sea-level change during the Holocene, both specifically in the Northern Territory (Woodroffe et al, 1987) and around other parts of Australia (Lewis et al, 2013), as well as elsewhere in the world (Toscano and Macintyre, 2003;Fontes et al, 2017). However, these sedimentary archives also provide insights into the way in which coastal wetlands have responded to sea-level change.…”
Section: Introductionmentioning
confidence: 99%